INTELLECTUAL DEVELOPMENT IN ANDREA HIRATA’S AYAH - Desiyanti, Dwi; Pawiro, Muhammad Ali; Ezir, Ely (Universitas Islam Sumatera Utara, 2024)
This research investigates the intellectual development of Sabari, the protagonist in Andrea Hirata's novel, Ayah, applying the theoretical framework proposed by Zubaedi (2013). Zubaedi outlines that character formation, as per the Ministry of National Education's grand design (2010), is a complex interplay of psychological and socio-cultural factors, encompassing cognitive, affective, conative, and psychomotor potentials. Within this framework, intellectual development is characterized by core traits such as intelligence, creativity, fondness for reading, and curiosity. Drawing upon theories of cognitive development and literature on intelligence, creativity, reading habits, and curiosity, the study aims to deepen understanding of Sabari's growth. Employing qualitative analysis, Sabari's actions and interactions within the narrative are examined to identify themes related to intelligence, creativity, fondness for reading, and curiosity. The analysis reveals Sabari's multifaceted intelligence, demonstrated through adept problem-solving, linguistic proficiency, emotional intelligence, and social awareness. Sabari's creativity is showcased in his resourceful problem-solving and innovative communication methods, such as using a turtle as a messenger. Additionally, Sabari's fondness for reading and curiosity drive his intellectual exploration and engagement with the world. Through thematic exploration, the research sheds light on the interconnectedness of intelligence, creativity, reading habits, and curiosity in shaping human cognition and behavior, with implications for education, psychology, and literature studies.